ATP bioluminescence can evaluate cleaning and sanitizing effectiveness in the milking parlor - M. J. Meyer; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 1997)
Four areas of the milking parlor were evaluated for effective cleaning and sanitation using total aerobic counts (standard plate count) and ATP bioluminescence (ATPB) techniques. Whereas the plate counts only monitor bacterial numbers, the ATPB results (reported as relative light units, RLU) also indicate residual soil or food residue on the surface. Results showed little correlation between the RLU values and the aerobic plate count data; however, the ATP bioluminescence system is a fast (<2>min) and simple method that evaluates the effectiveness of cleaning and sanitation procedures employed.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Milking parlor; HACCP plan; Sanitation; ATP bioluminescence; dairy